2016
DOI: 10.4014/jmb.1605.05016
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Usage of Nucleobase Triplets and Codon Context Pattern in Five Influenza A Virus Subtypes

Abstract: Influenza A virus is a single-stranded RNA virus with a genome of negative polarity. Owing to the antigenic diversity and cross concrete shift, an immense number of novel strains have developed astronomically over the years. The present work deals with the codon utilization partialness among five different influenza A viruses isolated from human hosts. All the subtypes showed the homogeneous pattern of nucleotide utilization with a little variation in their utilization frequencies. A lower bias in codon utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In NSVs, however, their CUB does not match that of the host cell despite their reliance on host protein translation. This phenomenon has previously been attributed to limiting CpG to evade the host's immune system and to the concept of codon constellation (8,12,(31)(32)(33). More importantly, analyses of codon usages revealed that CUB of NSVs did not result from transitional selection (34)(35)(36).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In NSVs, however, their CUB does not match that of the host cell despite their reliance on host protein translation. This phenomenon has previously been attributed to limiting CpG to evade the host's immune system and to the concept of codon constellation (8,12,(31)(32)(33). More importantly, analyses of codon usages revealed that CUB of NSVs did not result from transitional selection (34)(35)(36).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, it has also been noted that the viral CUB can be significantly different from the host CUB (8). While this is often attributed to the suppression of CpG codons for evading the host immune system (12), the correlation is not ubiquitously distributed throughout all NSVs. Other requirements for virus growth may place constraints on the evolution of NSVs.…”
mentioning
confidence: 99%
“…6). Deka et al reported three major clusters of influenza A virus genes [14]. A feasible relationship of porcine circovirus 3 to other circoviruses was found with hierarchical clustering among them [18].…”
Section: Discussionmentioning
confidence: 94%
“…Here are the reasons of choosing these subtypes. Even though the number of possible lAVs combinations is huge, given the fact that there are 18 types of HA genes and 11 types of NA genes (till the year of late 2017, from NCBI), it is interesting that very few have been reported to infect humans 23 . Common subtypes, such as H1N1, H1N2, H2N2, H3N2, and H5N1 2427 , were found to circulate around humans to cause seasonal flu.…”
Section: Methodsmentioning
confidence: 99%